Induksi Tunas Anggrek (Dendrobium taurinum) Secara In Vitro Dengan Penambahan Naphatale Acetid Acid (NAA) Dan Benzyl Amino Purin (BAP) - Janah, Erisa Miftakul; Anur , Alifiyan; Qur’ani, Nurul; Risda, Anis Satu (Universitas Wiralodra, 2025)
Orchids are part of the Orchidaceae family, which holds high ecological and economic value, particularly Dendrobium, which is highly sought after in the market. This study aims to induce shoots of Dendrobium taurinum orchids in vitro using the addition of Naphthalene Acetic Acid (NAA) and Benzyl Amino Purin (BAP). In this research, experiments were conducted using a Factorial Completely Randomized Design (CRD), involving different concentrations of NAA and BAP. The results indicate that the addition of NAA and BAP significantly affects the number of shoots produced, with the combination of 0.5 ppm NAA and 0.5 ppm BAP yielding the best results. Furthermore, the percentage of viable plantlets also showed satisfactory results, reaching 100% in several treatments. This research is expected to provide new insights into more efficient and quality orchid propagation techniques, and contribute to the development of more productive and profitable orchid cultivation for farmers and the floriculture industry